Nine draft genome sequences of Claviceps purpurea s.lat., including C. arundinis, C. humidiphila, and C. cf. spartinae, pseudomolecules for the pitch canker pathogen Fusarium circinatum, draft genome of Davidsoniella eucalypti, Grosmannia galeiformis, Quambalaria eucalypti, and Teratosphaeria destructans - Brenda D. Wingfield; Miao Liu; Hai D. T. Nguyen; Frances A. Lane; Seamus W. Morgan; Lieschen De Vos; P. Markus Wilken; Tuan A. Duong; Janneke Aylward; Martin P. A. Coetzee; Kasia Dadej; Z. Wilhelm De Beer; et al. (IMA Fungus)
Abstract This genome announcement includes draft genomes from Claviceps purpurea s.lat., including C. arundinis, C. humidiphila and C. cf. spartinae. The draft genomes of Davidsoniella eucalypti, Quambalaria eucalypti and Teratosphaeria destructans, all three important eucalyptus pathogens, are presented. The insect associate Grosmannia galeiformis is also described. The pine pathogen genome of Fusarium circinatum has been assembled into pseudomolecules, based on additional sequence data and by harnessing the known synteny within the Fusarium fujikuroi species complex. This new assembly of the F. circinatum genome provides 12 pseudomolecules that correspond to the haploid chromosome number of F. circinatum. These are comparable to other chromosomal assemblies within the FFSC and will enable more robust genomic comparisons within this species complex.